Isytiqāq Kabīr - M. Suryadinata (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
Language is a portrait of a culture. Through language, one can discern the civilization, social forms, community, and richness of a society. Among the crucial discussions in language is Isytiqaq, as it directly or indirectly influences culture and language. For example, Arabic, which is part of the Semitic languages, becomes unique with the presence of Isytiqaq. Understanding Isytiqaq allows one to comprehend the characteristic similarities in meanings for specific letters. It is one of the studies in language that can broaden the understanding of the meaning of a language. Studying Isytiqaq is a part of the language's own development.